Penerapan Zoedpuzzleizz Sebagai Kelas Klinis Disertai Metode Remote Blended Learning - Hartini Dewi (Ideguru: Jurnal Karya Ilmiah Guru, 2021)
The background of this research is that the clinical class is formed from the presence of students who did not complete with scores below the minimum completeness criteria at SMAN I Tumpang based on the semester credit system. The selection of the remote blended learning method was included in this study, because the situation and conditions of the Covid-19 pandemic required this school to follow government rules for learning online. The purpose of this study was to determine the percentage of completeness, feasibility, and creativity of students in the clinical class in implementing Zoedpuzzleizz accompanied by a remote blended learning method. The research method used is descriptive qualitative and quantitative methods. Based on the research results, it was concluded that: 1) the large percentage of students' creativity in studying physics in the clinical class was achieved 100% with the average value of skills in the clinical class of 85, which is the number above KKM is more than equal to 78. 2) The percentage of the implementation of the Zoedpuzzleizz application is accompanied by a remote blended learning method in catching up with the behind-the-scenes concepts that have been suffered by students in clinical classes, amounting to 90% of implementation for teachers and 89% for students. 3) The percentage of completeness of understanding physics learning achieved in the clinical class in the application of the Zoedpuzzleizz application is 100% with an average of 91.5.